Clinical Outcome Following Prolonged Neoadjuvant Chemotherapy and Delayed Surgery in Osteosarcoma Patients: An Evidence-based Clinical Review - Waluyo Sugito; Achmad Fauzi Kamal (Acta Medica Indonesiana)
Background: The incidence of osteosarcoma reached 16.8 cases annually at dr. Cipto Mangunkusumo Hospital in 1995-2008. Previous studies suggested that prolonged neoadjuvant chemotherapy followed by delayed surgery improves the clinical outcome. Prolonged neoadjuvant chemotherapy followed by delayed surgery commonly occurs in Indonesia, as diagnostic imaging and surgery waiting list will delay the surgery. The aim of this study is to observe the survival rate and the event-free survival rate of osteosarcoma patients with prolonged neoadjuvant chemotherapy and delayed surgery. Methods: This review included randomized controlled trials (RCTs), cohort studies, retrospective cohort studies, clinical trials, and reviews. Literature search was conducted through MEDLINE (PubMed search engine), Cochrane Central Register of Controlled Trial, and Scopus. The studies were screened and selected according to inclusion criteria by author and contributors independently. Results: Six studies were included in the qualitative synthesis of this study. Overall survival rate, event-free survival rate, histological response and recurrence as well as neoadjuvant chemotherapy duration, cycle and regiment were assessed in this study. Conclusion: Prolonged neoadjuvant chemotherapy and delayed surgery results in 5-years survival rate of 43.2% to 96.6% and 5-years event-free survival rate of 35.7% to 86.4%.